(untitled) (Baltic Journal of Sport and Health Sciences, 2015)
Background. Developing lower extremity muscles in a proportional shape plays an important role of balanced body movement. It is believed that special development of muscles which provide multidirectional movements of ankle will contribute to the increase of balance ability, and this may significantly support the improvement of technical skill performance in football. The aim of the research was to examine the ability to keep dynamic balance and ankle joint muscle strength in football players, and to prove the relation between the ankle joint muscle strength level and the dynamic balance ability of each foot. Methods. The participants were amateur footballers (n = 17, football experience 10 ± 1.4years, weekly training 12 ± 1.3 h). “WFQ-R poll” questionnaire was used to determine the participants’ dominant and non-dominant limb, the dynamic balance was assessed using “Tecnobody Pro-Kin Type B 252” (Italy) device and ankle joint muscle strength was measured using an isokinetic dynamometer “Cybex Norm” (USA). Results. Significant differences (p < .05) were found between limbs for ankle plantar flexors, in non-dominant limb plantar flexors were stronger. Dynamic balance ability for dominant foot was better in comparison with non- dominant foot. The correlation was found between ankle plantar flexors, evertors, invertors and between dorsal and plantar flexors for both limbs. Conclusions. Strength improvement of muscles affects the movement of the ankle dynamic balance positively, but for the development of static and dynamic balance, proprioceptive balance training is as effective as strength training. Keywords: lower limbs, peak torque, balance, asymmetry.